2011
DOI: 10.1096/fj.11-189381
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of amyloid fibrils on cell membranes: the importance of ganglioside GM1

Abstract: The interaction of amyloid aggregates with the cell plasma membrane is currently considered among the basic mechanisms of neuronal dysfunction in amyloid neurodegeneration. We used amyloid oligomers and fibrils grown from the yeast prion Sup35p, responsible for the specific prion trait [PSI(+)], to investigate how membrane lipids modulate fibril interaction with the membranes of cultured H-END cells and cytotoxicity. Sup35p shares no homology with endogenous mammalian polypeptide chains. Thus, the generic toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 69 publications
(90 reference statements)
6
95
0
Order By: Relevance
“…In this case, a sharp point is also drawn out from the target membrane, as is observed with short β 2 m amyloid fibrils, but instead of destroying the liposome, the destabilized, extruded membrane region is fused to the viral membrane. The cryoelectron tomography images of β 2 m fibril-membrane interactions presented here suggest that the cellular dysfunction associated with these and other fibrils or fibril-like assemblies (16)(17)(18)(19)(20)(21)27) involves direct bilayer disruption. This membrane damage might arise by direct interaction with the fibril ends and/ or by the creation of new, toxic species by reaction of the fibril ends with the lipids.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this case, a sharp point is also drawn out from the target membrane, as is observed with short β 2 m amyloid fibrils, but instead of destroying the liposome, the destabilized, extruded membrane region is fused to the viral membrane. The cryoelectron tomography images of β 2 m fibril-membrane interactions presented here suggest that the cellular dysfunction associated with these and other fibrils or fibril-like assemblies (16)(17)(18)(19)(20)(21)27) involves direct bilayer disruption. This membrane damage might arise by direct interaction with the fibril ends and/ or by the creation of new, toxic species by reaction of the fibril ends with the lipids.…”
Section: Discussionmentioning
confidence: 77%
“…In other cases, toxicity may reside with the amyloid fibrils themselves. Evidence that toxicity correlates with fibrillar assemblies has been reported for yeast and mammalian prion proteins (16,17), human lysozyme (18), Huntingtin exon 1, α-synuclein (19), and Amyloid-β (Aβ) (20,21). Furthermore, Aβ plaques have been shown to form rapidly in vivo and to precede neuropathological changes in a mouse model (22).…”
mentioning
confidence: 99%
“…found to be cytotoxic [3][4][5][6] or to induce the dysfunction of neurons and neuronal loss [7]. The binding of anle138b might inhibit aggregate growth and/or could reduce the toxicity of the aggregates and hamper disease progression as observed in in vivo experiments [16].…”
Section: Tablementioning
confidence: 99%
“…These aggregates, located in the brain of infected individuals, are characterized by a cross-β-sheet protein structure and a fibrillar morphology under the electron microscope. The amyloid aggregates are considered to play an important role in the pathogenesis of neurodegenerative diseases [3][4][5][6][7]. Furthermore, recent experiments pointed out that not only the fibrillar structures but especially the formation of smaller, highly cytotoxic oligomeric forms [8] might lead to neuronal loss [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the species formed during the aggregation reactions have a toxic effect on cells 5, 6, 7, 8. Several possible mechanisms of cellular damage have been identified with relative contributions that depend on both the concentrations and the types of aggregates present 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The aggregation process that results in the formation of oligomers may contribute to cellular damage 12, 13, 14, 15.…”
mentioning
confidence: 99%